Manifestasi Ibnu Hibban Terhadap Metodologi Penulisan Kitab Shahih Ibnu Hibban - Jasmit, Rudi Edwaldo; Kusuma, Febri (Multidisciplinary Journal of Religion and Social Sciences, 2024)
This article reviews the systematics, writing/compilation methods and introduces the book of Sahih Ibn Hibban in a more comprehensive manner which is different from the habits of the muhaddits in compiling their works in the collection of Hadith of the Prophet sallallaahu 'alaihi wa sallam. This cannot be separated from his background and his motives (goals) in collecting and compiling Hadith. In addition, Sahih Ibn Hibban in terms of its name is not as it is currently known by the public, because the original title of the book was "Al-Musnad al-Sahih 'ala al-Taqasim wa al-Anwa' min Ghayr al-Wujud Qat' fi Sanadiha wa La Tsubut Jarh fi Naqiliha" or "al-Taqasim wa al-Anwa'". However, the name Sahih Ibn Hibban is considered more famous and easy not only for Hadith experts but also among the general public. The book is not arranged by chapters and not in musnad form, but is compiled by classifying the Hadith of Rasulullah sallallah 'alaih wa sallam into 5 (five) parts (qism) where each part is further classified into several nau' or anwa' (kinds), and in each nau' there are various kinds of knowledge, namely the Hadiths of Rasulullah sallallah 'alaih wa sallam. Even though Ibn Hibban's book has appeared in recent times, scholars and Hadith experts have included it as an important book of Hadith, so that the scholars have paid great attention to it in the form of rearranging it into chapters like the systematic writing and compilation of the Hadith of the majority of muhaddits as done by 'Ala` al-Din 'Ali b. Balban al-Farisi then named his work Al-Ihsan fi Taqrib Sahih Ibn Hibban or also known as Sahih Ibn Hibban bi Tartib Ibn Balban, totaling 18 volumes. Then, some mu'assirin (contemporary) scholars among the muhaqqiq (tahqiq experts) such as Sheikh Ahmad Syakir and Sheikh al-Albani made ta'liq on Ibn Balban's book. And what al-Albani did was to summarize and perfect the book of al-Ihsan al-Amir 'Ala` al-Din al-Farisi in the form of useful penta'liqan and pentakhrijan of the Hadiths issued by Ibn Hibban. Likewise, Sheikh Muhaqqiq Syu'aib al-Arna`ut made tahqiq over him.